Direct conversion of N2 to nitrogen-containing organics via a plasma-electrochemical cascade reaction approaching 100% yield - Wenjie Wu; Ao Qin; Cairong Wang; Ta Thi Thuy Nga; Leitao Xu; Yandong Wu; Ruiqi Wang; Zhongcheng Xia; Zhonghuan Zhu; Yulu Yang; Chuang Fu; Chung-Li Dong; et al. (Science Bulletin, 2026)

Unveiling Mo doping effects in hydrated vanadium oxide cathodes for high-energy zinc-ion batteries: Evidence from operando synchrotron X-ray and DFT analysis - Sanna Gull; Hsu-Chen Cheng; En-Hao Li; Tsung-Yi Chen; Chung-Sheng Ni; Wan-Ju Yu; Hao-Hsiang Chang; Ai-Yin Wang; Ruey-An Doong; Chin-Lung Kuo; Yu-Chun Chuang; Bo-Hao Chen; et al. (Chemical Engineering Journal, 2026)

Long-range transport and source apportionment of marine fine particles in the Taiwan Strait and South China Sea Intersection: Spatiotemporal variations and chemical fingerprints - Chung-Shin Yuan; Hsueh-Lung Chuang; Yu-Lun Tseng; Tsung-Chang Li; Ker-Yea Soong; Wen-Hsi Cheng (Atmospheric Environment, 2024)

Source apportionment of PM2.5 episodes in the Taichung metropolitan area, Taiwan - Ming-Tung Chuang; Charles C.-K. Chou; Chuan-Yao Lin; Wei-Che Lin; Ja-Huai Lee; Meng-Hsuan Li; Wei-Nai Chen; Chih-Chung Chang; Chian-Yi Liu; Yi-Chun Chen (Atmospheric Research, 2024)

Crystal orientation control in angstrom-scale channel membranes for significantly enhanced blue energy harvesting - Chia-Hui Chuang; Yu-Hsiang Peng; Chung-Kai Chang; Po-Ya Chang; Dun-Yen Kang; Li-Hsien Yeh (Chemical Engineering Journal, 2024)

Correction to: Effects of Long-term Climate Change on Typhoon Rainfall Associated with Southwesterly Monsoon Flow near Taiwan: Mindulle (2004) and Morakot (2009) - Chung-Chieh Wang; Li-Shan Tseng; Chien-Chang Huang; Pi-Yu Chuang; Nan-Chou Su; Cheng-Ta Chen; Shih-How Lo; Kazuhisa Tsuboki (Asia-Pacific Journal of Atmospheric Sciences, 2024)

Spatiotemporal characterization of PM2.5, O3, and trace gases associated with East Asian continental outflows via drone sounding - Chih-Yuan Chang; Jia-Lin Wang; Yen-Chen Chen; Wei-Nai Chen; Sheng-Hsiang Wang; Ming-Tung Chuang; Neng-Huei Lin; Charles C.-K. Chou; Wei-Syun Huang; Li-Jin Ke; Xiang-Xu Pan; Yu-Jui Ho; et al. (Science of The Total Environment, 2024)

Effects of Long-term Climate Change on Typhoon Rainfall Associated with Southwesterly Monsoon Flow near Taiwan: Mindulle (2004) and Morakot (2009) - Chung-Chieh Wang; Li-Shan Tseng; Chien-Chang Huang; Pi-Yu Chuang; Nan-Chou Su; Cheng-Ta Chen; Shih-How Lo; Kazuhisa Tsuboki (Asia-Pacific Journal of Atmospheric Sciences, 2024)

Decoding the genome of bloodsucking midge Forcipomyia taiwana (Diptera: Ceratopogonidae): Insights into odorant receptor expansion - Ming-Der Lin; Chia-Hsien Chuang; Chih-Hsin Kao; Shu-Hwa Chen; Szu-Chieh Wang; Ping-Heng Hsieh; Guan-Yu Chen; Chun-Chia Mao; Jeng-Yi Li; Mei-Yeh Jade Lu; Chung-Yen Lin (Insect Biochemistry and Molecular Biology, 2024)

Application of proteomics in identifying crucial virulence factors shared by different Streptococcus iniae isolates for developing an effective subunit vaccine against S. iniae in tilapia - Chaio-Ping Chen; Shu-Chun Chuang; Kuan-Lun Su; Li-Kai Chen; Yi-Chen Lin; Yu-Jen Wu; Shang-Pin Liu; Shao-Wen Hung; Chung-Hwan Chen; Chung-Da Yang (Aquaculture, 2024)

Short-term mediating effects of PM2.5 on climate-associated COPD severity - Huan Minh Tran; Yuan-Chien Lin; Feng-Jen Tsai; Kang-Yun Lee; Jer-Hwa Chang; Chi-Li Chung; Kian Fan Chung; Kai-Jen Chuang; Hsiao-Chi Chuang (Science of The Total Environment, 2023)

The impact of air pollution on respiratory diseases in an era of climate change: A review of the current evidence - Huan Minh Tran; Feng-Jen Tsai; Yueh-Lun Lee; Jer-Hwa Chang; Li-Te Chang; Ta-Yuan Chang; Kian Fan Chung; Han-Pin Kuo; Kang-Yun Lee; Kai-Jen Chuang; Hsiao-Chi Chuang (Science of The Total Environment, 2023)

Utilizing Numerical Models and GIS to Enhance Information Management for Oil Spill Emergency Response and Resource Allocation in the Taiwan Waters - Chi-Min Chiu; Laurence Zsu-Hsin Chuang; Wei-Liang Chuang; Li-Chung Wu; Ching-Jer Huang; Yinglong Joseph Zhang (Journal of Marine Science and Engineering, 2023)
This study aims to establish a comprehensive workflow for developing emergency response plans for both actual and scenario oil spill incidents in the Taiwan waters while addressing the resource allocation for oil spill containment as well. This workflow comprises two vital components. The first component involves the integration of numerical tools and observational data, which includes the incorporation of wind data from sources such as the National Centers for Environmental Prediction (NCEP) or meteorological stations. Additionally, it incorporates ocean current data simulated by the semi-implicit cross-scale hydroscience integrated system model (SCHISM) into the general NOAA operational modeling environment (GNOME) model, which is a new approach for this purpose. In order to assess the efficacy of this component, two distinct case studies were conducted. The first case study focused on an incident in a northern coastal area of Taiwan under open sea conditions, whereas the second case study examined an incident within a major commercial harbor in central Taiwan. The second component of this workflow involves creating oil risk maps by integrating the results from the first component with specific geographical factors into Google Earth. These oil risk maps serve multiple purposes. They offer real-time information to emergency response commanders regarding oil spill hazard prediction, and they also enable the effective development of emergency response strategies and disposal plans for potential oil spill incidents. This is achieved by generating risk maps for various scenarios using the approach outlined in the first component. Additionally, these maps assist in the assessment and planning of resource allocation for oil containment.

Ambient relative humidity-dependent obstructive sleep apnea severity in cold season: A case-control study - Kuan-Jen Bai; Wen-Te Liu; Yuan-Chien Lin; Yansu He; Yueh-Lun Lee; Dean Wu; Ta-Yuan Chang; Li-Te Chang; Chun-Yeh Lai; Cheng-Yu Tsai; Kian Fan Chung; Kin-Fai Ho; et al. (Science of The Total Environment, 2023)

Importance of surface charge of soot nanoparticles in determining inhalation toxicity in mice - Ta-Chih Hsiao; Chia-Li Han; Tzu-Ting Yang; Yueh-Lun Lee; Yu-Fang Shen; Yu-Teng Jheng; Chii-Hong Lee; Jer-Hwa Chang; Kian Fan Chung; Han-Pin Kuo; Hsiao-Chi Chuang (Environmental Science and Pollution Research, 2022)

Bragg-region recognition of high-frequency radar spectra based on deep learning and image fusion processing - Laurence Zsu-Hsin Chuang; Yu-Ru Chen; Yu-Jen Chung; Li-Chung Wu; Tsung-Mo Tien (International Journal of Remote Sensing, 2022)

The impacts of ambient relative humidity and temperature on supine position-related obstructive sleep apnea in adults - Wen-Te Liu; Yuan-Hung Wang; Li-Te Chang; Chih-Da Wu; Dean Wu; Cheng-Yu Tsai; Chen-Chen Lo; Kang Lo; Kian Fan Chung; Ta-Yuan Chang; Kai-Jen Chuang; Yueh-Lun Lee; et al. (Environmental Science and Pollution Research, 2022)

How much of Typhoon Morakot's extreme rainfall is attributable to anthropogenic climate change? - Chung‐Chieh Wang; Li‐Shan Tseng; Chien‐Chang Huang; Shih‐How Lo; Cheng‐Ta Chen; Pi‐Yu Chuang; Nan‐Chou Su; K. Tsuboki (International Journal of Climatology, 2019)
Typhoon Morakot (2009), which made landfall in Taiwan during August 7–9, 2009, produced the highest rainfall and became the deadliest typhoon ever recorded in Taiwan since 1958. To assess the role of anthropogenic climate change in the typhoon‐related torrent, we compare the water budget between a pair of cloud‐resolving sensitivity experiments. The pair consists of a control simulation that reproduces Typhoon Morakot (2009) in current climate and a sensitivity simulation in which the same storm is placed in a slightly different climate background where the late 20th century anthropogenic climate change signal is removed. The anthropogenic signal is estimated with the CMIP5 experiments of 18 models for the period of 1985–2005, during which the global warming trend is discernible. In climate states that differ merely by a 20‐year mean anthropogenic change, Morakot (2009) yields 3.4–3.6% more total rainfall in the control experiment than its sensitivity counterpart within a radius of 300–500 km from the storm centre. Water budget analysis indicates that the increase in typhoon rainfall is mainly resulted from the enhanced convergence of vapour flux. The enhancement is, in turn, contributed by the increased tropospheric moisture due to global warming and, to a lesser extent, by a more active secondary circulation in the storm that is associated with the anthropogenic climate change.

High total volatile organic compounds pollution in a hospital dental department - Ming-Hui Liu; Tao-Hsin Tung; Fen-Fang Chung; Li-Chuan Chuang; Gwo-Hwa Wan (Environmental Monitoring and Assessment, 2017)

Baseline human papillomavirus infection, high vaginal parity, and their interaction on cervical cancer risks after a follow-up of more than 10 years - Shu-Fen Liao; Wen-Chung Lee; Hui-Chi Chen; Li-Chung Chuang; Mei-Hung Pan; Chien-Jen Chen (Cancer Causes & Control, 2012)

Ocean remotely sensed image analysis using two-dimensional continuous wavelet transforms - Li-Chung Wu; Laurence Zsu-Hsin Chuang; Dong-Jiing Doong; Chia Chuen Kao (International Journal of Remote Sensing, 2011)

Quantification of non-homogeneity from ocean remote-sensing images using two-dimensional continuous wavelet transforms - Li-Chung Wu; Laurence Zsu-Hsin Chuang; Dong-Jiing Doong; Chia Chuen Kao (International Journal of Remote Sensing, 2011)

Association between human papillomavirus and adenocarcinoma of rectum and recto-sigmoid junction: a cohort study of 10,612 women in Taiwan - Li-Chung Chuang; Hui-Chi Chen; San-Lin You; Ching-Yu Lin; Mei-Hung Pan; Yi-Chun Chou; Chang-Yao Hsieh; Chien-Jen Chen (Cancer Causes & Control, 2010)

TCF7L2 genetic variants and progression to diabetes in the Chinese population: pleiotropic effects on insulin secretion and insulin resistance - Yi-Cheng Chang; Yen-Feng Chiu; Larry Low-Tone Ho; Chih-Tai Ting; Kuang-Chung Shih; J. David Curb; Yii-Der Ida Chen; Hung-Yuan Li; Lee-Ming Chuang (Journal of Molecular Medicine, 2010)

Nonlinear influences on ocean waves observed by X-band radar - Li-Chung Wu; Dong-Jiing Doong; Beng-Chun Lee; Laurence Zsu-Hsin Chuang; Chia Chuen Kao (Marine Geophysical Research, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)